Antimicrobial, Antiradical Activity, and X-Ray Fluorescence Spectroscopy Analysis of Aloe otallensis Plant Used in Traditional Medicine in Southern Ethiopia - Yonas Syraji; Mulugeta Kebebew; Yohannis Techane; Dawit Albene (International Journal of Microbiology)
Medicinal plants have a long history of treating diseases in animals and humans in Ethiopia. Nevertheless, not enough research has been done on the antibacterial properties and possible bioactive components of the majority of medicinal plants. Therefore, this study was concerned with the evaluation of the percentage yield, phytochemical, antimicrobial, antifungal, MIC, antiradical activities, phenolic content, and X-ray fluorescence spectroscopy (XRF) analysis of A. otallensis plant extracts. The mean values of antimicrobial, antifungal, MIC, antiradical, phenolic content, and XRF analysis were reported as mean ± standard deviation. The solvent methanol showed a higher degree of yield in leaf and root extract which was 8.45 (22.27%) and 3.12 g (15.58%), respectively, while distilled water extract of leaf and root showed less degree of yield which was 0.22 g (1.10%) and 0.42 g (2.1%), respectively. Qualitative phytochemical analyses of the plant parts have revealed the presence of various components of metabolites like alkaloids, flavonoids, phenol, saponins, tannins, steroids, steroids, terpenoids, triterpenoids, glycosides, anthraquinones, diterpenes, phytosterols, and phlobatannals. A. otallensis gel extracts had shown significant antibacterial and antifungal activity against the test bacterial and fungus, respectively. Moreover, the methanolic gel extracts of A. otallensis demonstrated notable antiradical activity than the leaf and the root. The highest value of phenolic content was obtained in A. otallensis; gel, leaf, and root extract which was 61.9 ± 0.5 mg/g, 53.6 ± 0.3 mg/g, and 51.6 ± 0.6 mg/g, respectively. In this study, twelve elements in the plant parts of A. otallensis were determined using XRF spectroscopy. Overall, this research contributes to the understanding of the pharmacological potential of A. otallensis and highlights the importance of further research into its medicinal properties. The results provide valuable insights into the use of medicinal plants to treat diseases and support the development of natural therapeutics.